Immigration, Occupational Choice and Public Employment - Luca Marchiori; Patrice Pieretti; Benteng Zou (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
This paper investigates the theoretical effects of immigration in an occupational choice model with three sectors: a low-skilled, a high-skilled and a public sector. The originality of our approach is to consider (i) intersectoral mobility of labor and (ii) public employment. We highlight the fact that including a public sector is crucial, since omitting it implies that low-skilled immigration unambiguously reduces wages and welfare of all workers. However, when public employment is considered, we demonstrate that immigration increases wages in the high-skilled and the public sectors, provided that the immigrant workforce is not too large and the access to public jobs is not too easy. The average wage of natives may also increase accordingly. Moreover, immigration may improve workers' welfare in each sector. Finally, the mechanism underlying these results does not require complementarity between natives and immigrants.
Keywords: J24; J61; J45; H44; 330; Immigration; occupational choice model; public employment